PERAN SEKTOR LAPANGAN USAHA SEBELUM DAN SETELAH COVID-19 TERHADAP EKONOMI DI KABUPATEN OGAN KOMERING ILIR MENGGUNAKAN DATA PDRB ADHK 2010 - Alfarisi, M. Salman; Mayeza, Zalwa; Sowando, M Alif; Prasaja, Ahmad Syukron (JURNAL BISNIS KOLEGA, 2023)
In general, business fields have the goal of improving people's welfare, the formation of business fields will create jobs so that the unemployment rate will decrease. The business field is an important thing in an area where currently it is related to economic growth, this business sector has a major impact on the economy. The business sectors are agriculture, processing industry, electricity, gas and drinking water, buildings, trade, hotels and restaurants, transportation and communications, finance, leasing and corporate services, as well as other services. From these sectors it is clear that this cannot be separated from the factors of the progress of a regional economy. The benchmark for the success of the business field is seen from the growth and structure of the business field. Ogan Komering Ilir Regency (OKI) is ranked the 6th most densely populated area in the province of South Sumatra with a population of around 731,721 people, all of them need jobs, if there are few business fields, the poverty and unemployment rates will increase. And it is certain that the field of business is very important to support the prosperity of the Indonesian people.